Hexagonal map grids – an experimental study on the performance in memory of object locations. Issue 5 (3rd September 2019) - Edler, Dennis; Keil, Julian; Bestgen, Anne-Kathrin; Kuchinke, Lars; Dickmann, Frank
ABSTRACT: In various every day contexts, maps are used as media supporting orientation, wayfinding, and navigation tasks. To create highly accurate and reliable maps, cartographers must be aware of cognitive effects that occur when people process map information. Interdisciplinary research from cognitive psychologists showed that map graphics lead to spatial distortions in human spatial memory. These distortions can influence human orientation capacities. Recently, it was discovered that grid structures overlaid on maps help to correct spatial distortions in cognitive representations of geographic space. Square grids chunk a map into smaller units (regions). They guide map-viewing behavior, and their regular structure helps map users to recall learned locations of objects more accurately. The effects caused by square grids may also occur when overlaying other common kinds of geometries, such as hexagonal structures. The effects of hexagonal grid structures on memory of object locations were investigated in this map-experimental study. The study design is based on a recall-memory-paradigm, an established method of experimental psychology to measure performance in memory. The results show that hexagonal grid patterns can improve the performance.